Analysis of the COVID-19 pandemic data across different states and union territories of India and effectiveness of the lockdown. (5th January 2022) - Gupta, Sunil; Gabrani, Goldie; Phutela, Nishtha
With the onset of March 2020, India has stared witnessing the pandemic caused by COVID-19. However, the effect of this pandemic is not the same across different states of India. In this paper, the authors have carried out detailed analysis to get the complete view of the severity of COVID-19 disease in various states of India and have tried to find out the impact of various preventive measures like lockdown on its containment. The analysis will help various agencies to take appropriate, rigorous, and continuous measures to overcome this great health challenge.